GAMBARAN KONSUMSI MAKANAN KARIOGENIK PADA SAAT ISTIRAHAT DI SD NEGERI 130 PALEMBANG - Meyrisa Bastari (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Palembang, 2019)
One of the factors causing dental caries is cariogenic food, the habit of children consuming cariogenic foodssuch as chocolate, sweets, cakes and so on, because the interesting shape of the food and the taste is delicious,so it is favored by children. This study was conducted to obtain an overview of the consumption of cariogenicfoods at the SD Negeri 130 Palembang. The method used in the study is descriptive with the same sample with apopulation of 843 children. This data collection was carried out in April 2019. Data were analyzed usingunivariate analysis. The results of the study were based on the number of children who consumed cariogenicfoods as many as 461 people or 55% of children, while the number of children who did not consume cariogenicfood was 382 people or 45% of children. From this study it was concluded that the number of children whoconsumed cariogenic foods was greater than the number of children who did not consume cariogenic foods atthe SD Negeri 130 Palembang.